Mechanical Interlocking Approaches to the Prediction of Mechanical and Tribological Behavior of Natural Fiber-Reinforced Polymer Hybrid Nanocomposites or Automotive Applications - R. Venkatesh; P. C. Santhosh Kumar; A. Senthilkumar; J. Phani Krishna; P. Chandramohan; V. N. Aneesh; Avinash Malladi; C. B. Priya; Elangomathavan Ramaraj (Advances in Polymer Technology)
Polymer matrix composites synthesized with biodegradable natural fiber obtain a predominant structure with specific properties at a low-processing cost. The unique characteristics of polymer matrix composites were magnetized in automotive parts like top roof, panel, and seat frame applications. American Society for Testing and Materials (ASTM) G99 analyzed the wear characteristics of synthesized composites through a pin-on-disc wear tester with an EN32 steel disc. The epoxy hybrid composites have been synthesized via a conventional casting process assisted with a mechanical interlock technique to obtain a predominant structure with specific properties at a low-processing cost. The advanced composite contained different jute weights (50, 25, 50, and 75 g) and coconut coir (50, 70, 45, and 20 g) hybridized with graphite particles. ASTM D2240, D638, and D790 standards evaluated the fabricated composite hardness, tensile, and flexural strength. The Sample 4 hybrid composite found maximum hardness, tensile, and flexural strength of 27.41 ± 0.99 Hv, 51.69 ± 1.01MPa, and 55.94 ± 0.78 MPa, respectively. Sample 4 offered good wear resistance of their volumetric wear rate of 0.043 cm3 on 40 N average load at 0.25 m/s sliding speed. It is increased by 12% compared to Sample 1 at 40 N applied load on 2.5 m/s sliding speed.